2011
DOI: 10.1590/s1808-86942011000300004
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of tinnitus in mp3 player users

Abstract: Exposure to loud noise is one of the main causes of tinnitus. Aim: To analyze the incidence of tinnitus in mp3 player users and non-users. Material and method: One hundred subjects aged from 15 to 30 years were enrolled, 54 of them were regular mp3 player users and 46 were not. Patients with continuous tinnitus for at least 6 months completed the Tinnitus Handicap Inventory (THI) and were tested with high frequency audiometry and transient-evoked otoacoustic emissions (TAOE). Study design: A cross-sectional co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
29
1
5

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 17 publications
(32 reference statements)
5
29
1
5
Order By: Relevance
“…Various studies have found that exposure to music at a high intensity is likely to be associated with several hearing symptoms, such as TTS, tinnitus, hyperacusis, recruitment, distortion or abnormal pitch perception,eventually resulting in permanent hearing loss (Zhao et al, 2010, Rice et al, 1987, Meyer-Bisch, 1996, Petrescu, 2008, Figueiredo et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have found that exposure to music at a high intensity is likely to be associated with several hearing symptoms, such as TTS, tinnitus, hyperacusis, recruitment, distortion or abnormal pitch perception,eventually resulting in permanent hearing loss (Zhao et al, 2010, Rice et al, 1987, Meyer-Bisch, 1996, Petrescu, 2008, Figueiredo et al, 2011.…”
Section: Introductionmentioning
confidence: 99%
“…The problem can also cause extra-auditive damage, such as sleep disorders, cardiovascular disorders, stress, fatigue, tension, irritability, inattention, tiredness, nervousness, headache, and arterial hypertension 7,8 . According to the American Speech Language Hearing Association (ASHA), 61% of American teenagers have personal stereos 9,10 , while 51% of students in American high schools have symptoms of hearing loss. An interesting part of that study was the fact that most students prefer high volumes, as adults tend to use more moderate volumes.…”
Section: Introductionmentioning
confidence: 99%
“…A number of papers published recently estimated the risk of hearing loss due to the use of PMPs, as well as the actual incidence of hearing loss and tinnitus in the exposed populations. The studies were carried out in German, American, Italian, Dutch, Slovenian, Brazilian, and Malaysian teenagers and young adults [14,15,16,17,18,8,19].…”
Section: Discussionmentioning
confidence: 99%